Enhancing quality of life and medication adherence for people living with HIV: the impact of an information system - Maria Panayi; Georgios K. Charalambous; Eleni Jelastopulu (SpringerOpen, 2024)
Abstract Background The widespread availability of antiretroviral therapy has led to improvements in life expectancy and thus an increase in the number of people living with HIV/AIDS (PLWHA) worldwide. However, a similar increase in the number of newly-diagnosed patients in Cyprus suggests the need for solutions designed to improve monitoring, planning, and patient communication. In this study, we aimed to determine whether the use of an information system to manage PLWHA might contribute to improved quality of life and critical adherence to prescribed drug regimens and ongoing medical care. Methods A randomized controlled trial study was conducted in Cyprus based on information that we collected using the highly valid and reliable Greek translation of the World Health Organization (WHO) Quality of Life (QOL) HIV-BREF questionnaire to assess sociodemographic variables and patient compliance. We distributed 200 questionnaires before implementing a Health Medical Care (HMC) information system at our clinic. Six months after implementing this system, 68 of the completed questionnaires were selected, including two groups of 34 participants who had been assigned at random to the intervention or the control group. Participants included PLWHA aged ≥ 18 years who had been receiving antiretroviral therapy for more than 12 months between July 15, 2020, and July 15, 2022. Results The changes in baseline to six-month scores reported for the intervention group were significantly higher than in the control group in all six subscales assessed with the WHOQOL-HIV-BREF questionnaire, as well as in the assessment of compliance. Furthermore, compliance with treatment was associated with higher scores in the questionnaire subscales, including physical health, psychological health, degree of autonomy, social relationships, life circumstances, and spirituality/religious/personal beliefs. We also identified specific demographic factors and behaviors that were associated with better compliance with scheduled medical care and the prescribed drug regimen. Specifically, men exhibited better compliance than women and younger PLWHA exhibited better compliance than the elderly as did individuals who reported a higher level of educational attainment. Additionally, individuals who did not use addictive substances, consumed less alcohol, and were managed using the monitoring information system all exhibited better compliance compared to those in the control group. Conclusion The results of this study suggest that management of PLWHA via the use of an information system can contribute to improved QOL and drug compliance.